Pengaruh Desain Produk, Celebrity Endorsement, dan Brand image terhadap Keputusan Pembelian Sepatu New Balance Tipe Lifestyle di Yogyakarta (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the influence of product design, celebrity endorsement, and brand image on the purchase decision of New Balance lifestyle shoes in Yogyakarta. The research employs a quantitative approach using a survey method. Data were collected by distributing questionnaires to 111 respondents selected through purposive sampling. Data analysis was conducted using SPSS 26 software. The data testing techniques used in this study include validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis to test the hypotheses proposed in the research. The results indicate that product design has a positive influence on purchase decisions, celebrity endorsement has a positive influence on purchase decisions, and brand image has a positive influence on purchase decisions.